The Appropriation of the Coaching With CARE Model With Preservice Teachers: The Role of Community. (November 2015) - Maloch, Beth; Wetzel, Melissa Mosley; Hoffman, James V.; A. Taylor, Laura; Pruitt, Alina; Vlach, Saba Khan; Greeter, Erin
This study is part of a longitudinal, multiphase study on development of literacy mentoring practices particularly with regard to the cooperating teacher. This paper reports on the findings from the first year of the study during which cooperating teachers (CT) participated in a master's program focused on coaching and mentoring while mentoring preservice teachers completing their elementary education degree inside a literacy specialization cohort. Drawing on observational and interview data and employing an activity theory framework, we examine the ways the CTs' involvement in a community of peers and faculty who met regularly in courses was instrumental their appropriation of a model of mentoring known as coaching with CARE. Analysis indicated that coursework, particularly two courses taken during the first year, offered multiple spaces that functioned as ways for participants to work through tensions that arose as the CTs moved across activity systems (from their coaching community at the university to their individual schools situated within area school districts). Specifically, these spaces afforded opportunities to work through understandings of the underlying theories and concepts related to reflective coaching, to share their experiences and beginning enactments of the coaching model, and to coach one another as they interacted around videotaped coaching conferences.